Planned cesarean section vs planned vaginal delivery among women without formal medical indication for planned cesarean section: A retrospective cohort study of maternal short‐term complications. (15th July 2022) - Dahlquist, Karin; Stuart, Andrea; Källén, Karin
Abstract: Introduction: Rates of delivery by cesarean section have gradually risen in many parts of the world, and it is regarded as a safe surgical procedure with expanded indications. We assessed maternal complications within 6 weeks postpartum after planned cesarean section and after planned vaginal delivery among patients without medical indication for cesarean section. Material and methods: This was a retrospective cohort study based on Swedish national registers and included 714 326 deliveries from 2008 to 2017. The study group consisted of cephalic, singleton, term pregnancies and excluded those with previous cesarean or pregnancy conditions that would qualify for cesarean section. We compared the risks of short‐term complications between planned cesarean section and planned vaginal delivery. We obtained adjusted risk ratios (ARRs) using modified Poisson regression models adjusting for maternal age, parity, body mass index, smoking, country of birth, and county. Results: The outcomes studied were infections and thromboembolism. In the planned cesarean section group ( n  = 22 855), 15% had a postpartum infection compared with 10% in the planned vaginal group ( n  = 691 471) (ARR 1.6; 95% confidence interval [CI] 1.5–1.6), and 0.08% vs 0.05% had a postpartum pulmonary embolism (ARR 1.7; 95% CI 1.0–2.6). The obtained risk estimates corresponded to "number needed to harm" estimates of 17 and 3448, respectively. When dividing the infections into subgroups, the risk of endometritis (ARR 1.2; 95% CI 1.1–1.3), wound infection (ARR 2.7; 95% CI 2.4–3.0), urinary tract infection (ARR 1.5; 95% CI 1.3–1.7), and mastitis (ARR 2.0; 1.9–2.2) was higher after planned cesarean section. Conclusions: Among patients without medical indication for planned cesarean section, the risks of short‐term maternal complications were higher with planned cesarean section than with planned vaginal delivery.